An improved dynamic model of suspended monorail train-bridge system considering a tyre model with patch contact. (October 2020) - He, Qinglie; Cai, Chengbiao; Zhu, Shengyang; Wang, Kaiyun; Zhai, Wanming
Highlights: An improved dynamic model of suspended monorail train-bridge system is developed and validated by the field test. A patch-contact tyre model is established and its key parameters are identified by a full-scale laboratory experiment. Comparison with point-contact tyre model reveals the advantage and significance of the patch-contact tyre model. Several key design parameters are selected optimally by comprehensively considering all vehicle-bridge dynamic indices. Abstract: This study aims to elaborately investigate the dynamic performance of suspended monorail train-bridge system (SMTBS) by establishing an improved train-bridge interaction model considering a tyre model with patch contact. First, to reasonably model the contact behaviour between tyre and bridge, a tyre model with patch contact is established by using the continuous radial spring-damping elements. Subsequently, the stiffness and damping performances of a driving tyre used in the SMTBS are studied based on a full-scale laboratory experiment, and then the parameter identification of the established patch contact tyre model is accordingly conducted with the test data. On this base, an improved integrated train-bridge interaction model considering the tyre model with patch contact is developed by using ANSYS parameter design language (APDL), and its reliability is also validated by the field test. Further, by a comparison of train-bridge dynamic responses between the point-contact tyre model and the patch contact tyre model under different conditions, some obvious discrepancies are pointed out, and the advantage and significance of the patch contact model are also revealed. Finally, by applying the proposed model, the train-bridge dynamic performance is studied systematically when a train travels on the curve bridge, revealing the curve negotiation characteristics of vehicle as well as the bridge vibration performance. Meanwhile, several key design parameters of vehicle subsystem are selected optimally by comprehensively considering all vehicle-bridge dynamic indices. The research results may be beneficial to the dynamic performance improvement and optimal design of the SMTBS.